ANALISIS PENGELOMPOKAN PROVINSI DI INDONESIA BERDASARKAN JUMLAH DESA/KELURAHAN MENURUT JENIS PENCEMARAN LINGKUNGAN HIDUP TAHUN 2024 MENGGUNAKAN PCA DAN K-MEANS CLUSTERING - Rahmadani, Afifah Nisa; Hidayat, revalinaputria; Riza, Fikri Ahmad; Simanungkalit, Ariel Muda; Sari, Surya Puspita; Effendi, Magdalena (BESTARI BPS Kalimantan Timur, 2025)
Environmental pollution is a critical issue in Indonesia due to its impact on public health and ecosystem sustainability. Variations in pollution conditions across provinces indicate the need for analyses that can comprehensively describe spatial patterns. This study aims to classify 38 provinces in Indonesia based on the number of villages and urban villages according to types of environmental pollution, including water, soil, air pollution, and areas without pollution, in 2024. The data were obtained from official publications of Statistics Indonesia (BPS). The analysis employed Principal Component Analysis (PCA) as a dimensionality reduction technique, followed by K-Means Clustering to group provinces with similar pollution characteristics. The initial analysis was supported by descriptive statistical exploration and data standardization. The PCA results show that two principal components explain 89.41% of the total data variance. The optimal number of clusters was determined using the Elbow method and Silhouette coefficient, indicating that a two-cluster solution provides the most appropriate clustering structure (Silhouette score = 0.40). The clustering results reveal differences in environmental pollution characteristics between provinces in western and eastern Indonesia. These findings provide an initial, area-based descriptive overview of environmental pollution distribution in Indonesia and can support regional environmental management and more targeted policy formulation.